Drip irrigation or reduced N-fertilizer rate can mitigate the high annual N2O+NO fluxes from Chinese intensive greenhouse vegetable systems. (1st September 2019) - Yao, Zhisheng; Yan, Guangxuan; Wang, Rui; Zheng, Xunhua; Liu, Chunyan; Butterbach-Bahl, Klaus
Abstract: In China, most farmers intensively producing vegetables in greenhouses use frequent flooding irrigation and apply excessive amounts of nitrogen (N) fertilizers. This results in low resource use efficiency and high environmental N losses, partly in the form of the potent greenhouse gas nitrous oxide (N2 O) or of the atmospheric pollutant nitric oxide (NO). For ensuring high vegetable productivity at lower environmental costs, it is crucial to develop efficient irrigation and fertilization strategies. Here we report on year-round measurements of N2 O and NO fluxes as well as crop yields for a greenhouse cucumber cultivation, comparing common farmers' practice with two alternative managements, i.e., drip fertigation (which reduced irrigation water amount to half of that used for flood irrigation) and reduction of chemical N application by 1/3. Soils managed by farmers' practice were an important source of atmospheric N-oxides, specifically with regard to N2 O. Annual emissions were 60.5 and 1.39 kg N ha −1 yr −1, respectively, for N2 O and NO, which were 2.40% and 0.05% of the applied N, respectively. Compared to the farmers' practice, N2 O emission factors under drip fertigation were decreased by 41%, while NO emission factors nearly doubled. Applying lower rates of N application reduced N2 O and NO emission factors by 43% and 40%, respectively. Differences in the N-oxides emission strength were primarily ascribed to changes in soil microbial N turnover processes, i.e., higher moisture conditions in soils managed by farmers' practice favored denitrification in a greater extent compared with soils fertilized by drip fertigation. We also showed that drip fertigation and reducing fertilization rates by 1/3 did not compromise vegetable yields, so that lower yield-scaled N2 O + NO emissions were calculated. Therefore, the replacement of farmers' practice by drip fertigation or by reducing the amount of N applied would help to secure productivity, while reducing the climate and air quality footprint of greenhouse vegetable production. Graphical abstract: Image 1 Highlights: The farmers' practice showed higher N2 O emission factors than the IPCC default value. Drip fertigation greatly reduced N2 O emissions in comparison to the farmers' practice. In comparison to the farmers' practice, drip fertigaton stimulated annual NO fluxes. Reducing N rates by 1/3 decreased annual N2 O and NO EFs by 43% and 40%, respectively. Drip fertigation or reducing N rates by 1/3 did not compromise vegetable yields.